Application of the Group Investigation (GI) Learning Model to Improve Student Learning Outcomes in the Introductory Demography Course - Muhassanah, Nur'aini; Listiya Kartika, Dwiani (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The aim of this research is to apply the Group Investigation (GI) learning model to improve student learning achievement in the Introduction to Demography course. This is done because student learning outcomes are not optimal and lectures are still conventional. This research was conducted in February – April 2024. This type of research is classroom action research which consists of 2 cycles, where each cycle has 4 stages, namely: planning, implementation, observation and reflection. This research was conducted on 13 students in the 4th semester of the mathematics study program for the 2023/2024 academic year who took the Introduction to Demography course. The data collection techniques used are tests and observations. Data was taken from three activities, namely pre-cycle, cycle I and cycle II. The learning outcome data obtained by students at the pre-cycle stage was with an average score of 62.2 and a score above 65 reaching 53.8%, the first cycle experienced an increase with an average score of 69.2 with a score above 65 reaching 84 .6%, and cycle II obtained an average score of 79.9 and student scores above 65 reached 92.3% of students. In this research, it can be concluded that the application of the group investigation learning model can improve student learning outcomes in the Introduction to Demography course.